THE INFLUENCE OF THE CHOSEH SPECIALTY ON THE LEVEL OF PHYSICAL ACTIVITY OF STUDENTS - Borysevych, L. V.; Shukatka, O. V. (Rehabilitation and Recreation, 2022)
Article outlines the influence of the lifestyle, the chosen specialty and the cognition of motion meaning for health on increasing the level of physical activity. Since rapid development of civilization led to the quick change of life conditions, physical activity of many people began significantly decreasing, and some do not even have it at all. Cars and the Internet improve and facilitate the life of a modern person as a «disservice». Everyone can ride and everything can be ordered without leaving the place, and even more, it became possible to visit museums and exhibitions, as well as study and work online. Thus, a person, if one wishes, does not have to make any effort on oneself at all. However, there are some factors that in one way or another affect the way of life and this influence is positive, they force a person to be both active and conscious. After all, the cognition of the fact how physical activity influences on strengthening and saving health and motivate young people to actions. Depending on the specialty the student has chosen, its specificity requires one way or another, some actions. Moreover, for somebody this specialty requires more physical activity than others do. Thus, choosing future profession affects the human activity and lifestyle adaptation to it. As the poll showed, physical activity, in many of its manifestations, is present in the majority of those from whom the circumstances require it, that is, the chosen future profession. Only then comes the aware-ness and the necessity in physical activity. Those, who do not put any requirements or do not have any understanding or need in activity, do not want to increase it, at the expense of efforts on themselves, justifying themselves with a lack of time or something like that. In addition, the main our task is the work over the formation of motivation in student’s youth and the need of physical activity not depending on the chosen specialty and the lifestyle. After all, healthy youth is the successful future of any country.